Composite finite-time straight-line path-following control of an underactuated surface vessel. Issue 16 (November 2020) - Hou, Qiankang; Ma, Li; Ding, Shihong; Yang, Xiaofei; Chen, Xiangyong
Abstract: Aiming at steering an underactuated surface vessel (USV) with a shortest distance and lowest fuel cost to sail along the predetermined paths, this paper investigates the straight-line path-following problem for the USV in the presence of the disturbance, including system uncertainties, parameter perturbations and external disturbance, etc. First of all, by assuming that the disturbance does not exist, a state-feedback controller is designed for the path-following system by using finite-time control technique. Considering the facts that the yaw velocity of USV is usually not easy to be detected and the disturbance heavily affects the performance of the path-following system, a composite control method is developed in the presence of the disturbance to further improve the control performance by combining the finite-time differentiator (FTD) and the state-feedback controller. Owing to the disturbance estimation ability of FTD, the disturbance can be well compensated in real time, which implies that the robustness property of the closed-loop path-following system under the composite control scheme can be significantly improved. Finally, the simulation results are presented to verify the feasibility and effectiveness of the proposed algorithms.